Pengaruh Penerapan Pendekatan TPACK Berbantuan E-Modul Hidrokarbon terhadap Kemampuan Berpikir Kritis Peserta Didik Kelas XI di SMA Negeri 3 Lubuk Basung - Rahimah, Nikmatur; Yerimadesi, Yerimadesi (MASALIQ, 2025)
This study aims to analyze the effect of implementing the TPACK approach with the help of hydrocarbon e-modules on students' critical thinking skills at SMAN 3 Lubuk Basung. The research method used is a quasi-experiment with a non-equivalent control group design. The population consists of 41 students of class XI MIPA 1 and XI MIPA 2 of SMAN 3 Lubuk Basung in the 2023/2024 academic year. Samples were taken from the entire population by sampling using a saturated sampling technique. The research instrument was in the form of test questions arranged based on indicators of critical thinking skills. The results of the data analysis showed normal and homogeneous data and the hypothesis test showed tcount> ttable so that H0 was rejected and H1 was accepted. In other words, the implementation of the TPACK approach with the help of hydrocarbon e-modules can improve the critical thinking skills of class XI students at SMAN 3 Lubuk Basung.